Development of the Mechanism of Diversification of Resources Used by Enterprises of the Agricultural Complex in a Strategic Perspective - Muterko, H.; Havrylov, O.; Riabka, V. (Економічний вісник Донбасу, 2023)
Topicality. In the context of globalization of the world economy, enterprises of different industries, associated with the interpenetration of technology and capital, are diversifying their financial and economic activities. The effectiveness of its implementation directly depends on the timely focus on the types of goods, works, services that are in demand and competitive. Research on the competitiveness of products of various sectors of the economy is becoming increasingly important. The production of competitive products and ensuring the sustainable position of small and medium-sized enterprises in the agricultural market requires a change in production costs by creating a perfect management accounting system, which provides internal users with information for effective management. After all, the level of competitive products and the results of economic activity of the enterprise largely depend on the level of costs. Aim and tasks. The purpose of writing this study is to identify areas for improving the mechanism of diversification of resource use and cost management in small and medium-sized businesses. Research results. In order to effectively implement the diversification mechanism in the complex of agricultural enterprises, it is necessary to solve a number of micro- and macroeconomic problems. Particular attention should be paid to determining areas for improving the organizational and economic mechanism for diversification of resources used and cost management. The sphere of agriculture as animal husbandry, which remains one of the main branches of agriculture of small and medium business, in relation to the production of competitive products, is studied. Despite the large amount of research, the issues of regulation and optimization of livestock production costs in the management accounting system remain unclear. Theoretical and methodological developments aimed at determining the methods of regulation and optimization of costs for livestock production in the management accounting system, which determines the relevance of the selected topic. The regulation and optimization of costs for livestock production in the management accounting system, the expansion of the concept of «costs», methods of accounting for livestock costs and the main points of cost accounting in production. The production of competitive products and ensuring a stable position of enterprises in the agricultural market requires a change in the cost of livestock products by creating a perfect management accounting system that allows internal users to provide information for effective management. It is noted that in theory and practice there are a number of features of the classification of costs, which take into account various aspects of the agricultural enterprise and form a variety of information for effective management decisions. Thus, experience and research show that the organization of management accounting within a particular agricultural enterprise, focused on meeting the specific information needs of the management system, will ensure its success in dynamic economic conditions and help solve a wide range of problems to optimize livestock production costs. Conclusions. Based on the study, it can be stated that the improvement of the diversification mechanism should be defined as a set of methods and forms of management activities aimed at identifying and rational use of the most profitable opportunities to achieve the goals. The management system of production diversification includes methods and procedures of analysis, planning and control, as well as feedback, which allows to improve the quality of management decisions. Further research has been formed on the formation of a system of accounting for the cost of livestock products, capable of generating information flows for management decisions, which requires a sound approach to determining the objects of accounting and costing, establishing their relationship and interdependence.